1994
DOI: 10.1097/00132586-199412000-00069
|View full text |Cite
|
Sign up to set email alerts
|

A New Method of Veno-Venous Bypass during Human Orthotopic Liver Transplantation

Abstract: Veno-venous bypass is commonly used during orthotopic liver transplantation, but there is some controversy as to whether it contributes to a better outcome. Low shunt Jlows frequently reduce the eficacy of portofemoro-axillary systems and so a percutaneous cannulation technique for the subclavian and femoral vein with large bore catheters was developed in order to facilitate bypass management. This study reports the performance and complications of a portofemoro-subclavian bypass system during the anhepatic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…However, it has been shown that even with a heat exchanger incorporated into the system and normothermia there was no reduction in blood transfusion requirement or haemodynamic instability after reperfusion 7 . Other modifications of the venovenous bypass such as puncturing technique might eliminate the inconvenience of direct cutdown of femoral and subclavian veins 24 , but could not avoid the risk of air embolism, major bleeding and activation of the systemic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that even with a heat exchanger incorporated into the system and normothermia there was no reduction in blood transfusion requirement or haemodynamic instability after reperfusion 7 . Other modifications of the venovenous bypass such as puncturing technique might eliminate the inconvenience of direct cutdown of femoral and subclavian veins 24 , but could not avoid the risk of air embolism, major bleeding and activation of the systemic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous cannulation for bypass offers advantages in terms of surgical time and better flow rates during VVBP and has been reported to be a safe technique. 2,3 Central venous cannulation in general is a safe procedure, and complications of the technique are rarely life threatening. 4 However, deaths occur as a direct result of this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…None of the previously published series of percutaneous cannulation reported major complications, although they report on smaller series. [1][2][3][7][8][9][10] However, a study that reviewed the safety of percutaneous insertion of large-bore cannulae for extracorporeal life support in 94 patients reported 1 death that was the direct result of perforation of the SCV by the cannula. 11 NOTE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the percutaneous placement of the femoral cannulae with an axillary vein cut-down' and the percutaneous place- Copyright o 7 996 by the American Association for the Study of Liver Diseases ment of both cannulae have been described. [8][9][10] In 1993, prior to the publication of these reports, we began placing both the femoral vein drainage catheter and a left subclavian vein return catheter using a percutaneous double Seldinger technique. In this report we review our experience with both the cut-down ("open") and percutaneous methods of bypass cannulation.…”
mentioning
confidence: 99%